Innovation Policy - Joshi,Amol (2014)
This entry outlines the concept of innovation policy in the domain of strategic management. First, an overview of the history, goals and underlying principles of innovation policy is presented. Next, the primary functions and possible means of implementing innovation policy are described with an emphasis on theoretical foundations. Finally, the evaluation of innovation policy outcomes, including the intended and unintended consequences of policy changes, are briefly discussed.
Keywords: Strategy & Entrepreneurship